Are You Ready to Tie the Knot? A Quick Checklist - Lisa M. Leslie; Victor W. Harris (EDIS, 2012)
The inventor, statesman, and scholar Benjamin Franklin provided some wise advice to all those thinking about tying the knot. “Keep your eyes wide open before marriage,” he said, “[and] half shut afterwards.” Marriage is a partnership that has emotional, financial, and legal implications. Before entering into this union, it is important for you and your partner to have your “eyes wide open” as you examine your individual attitudes and behaviors about both social and financial issues. This 4-page fact sheet was written by Lisa M. Leslie and Victor W. Harris, and published by the UF Department of Family, Youth and Community Sciences, August 2012.